EVALUATION OF INTERNAL CONTROL FINANCING MUDHARABAH (CASE STUDY ON BPRS DANA AMANAH SURAKARTA) - Jettie Risniawatie, Endang Masitoh W, Siti Nurlaela (ITB AAS INDONESIA, 2017)
Financing in Islamic banks is one of the backbone of banking activities, because that's where the industry can survive and thrive. A company or institution that has run well should monitor the activities and results. Internal controls can be monitored either by means of a special assessment or aligned with business management. Internal control is required by bank management, because with a good internal control weaknesses will be able to protect people and reduce the likelihood of errors and discrepancies that might occur. This research is a field research conducted in BPRS Dana Amanah in Surakarta. This research method is descriptive qualitative research. This study aims to determine how the internal control procedures of financing and how the application of internal control of financing. The type of data collected in the form of qualitative data and consist of primary data and secondary data. Data collection methods such as interviews, observation, and documentation with qualitative data analysis. Control of BPRS Dana Amanah is reflected in the analysis of financing, Divison of duties, Dual Control, Joint / Dual Custody, Number Control and Balancing Independence. The conclusion of this study is the procedure of financing on the BPRS Trust Fund in accordance with the theory that the financing of the request until the disbursement of funds has no control by each officer. Internal control procedures of BPRS Dana Amanah for financing analysis was consistent with the theory, division of duties is not appropriate because there are geminating duties and functions. Dual control, joint / dual custody, number control, and independence balancing BPRS Dana Amanah have been applied and in accordance with the theory.Key words: Sharia Bank, Mudharabah, Internal Control.